Two milligrams IV hydromorphone is efficacious for treating pain but is associated with oxygen desaturation - Chang, MD, MS, Andrew K.; Bijur, PhD, Polly E.; Napolitano, MD, Antonio; Lupow, MD, Jason; Gallagher, MD, E. John (Journal of Opioid Management, 2018)
Objective: To evaluate the safety and efficacy of a single dose of 2 mg IV hydromorphone administered to emergency department patients in acute severe pain. Design: Prospective interventional. Setting: Urban academic emergency department. Patient, participants: Nonelderly adults (21-64 years old) with acute severe pain and baseline oxygen saturation (SO2)≥95 percent. Interventions: Two milligrams IV hydromorphone administered over 2-3 minutes. Main outcome measures: The primary outcome was use of naloxone as a reversal agent. Secondary outcomes included degree of pain relief as measured on a numerical rating scale, frequency of oxygen desaturation (SO2 < 95 percent), and side effects. Results: Of the 269 patients, none received IV naloxone. Median pain scores fell from 10 (worst pain possible) at baseline to 1 within 5 minutes and to 0 (no pain) at 30 minutes. SO2 was ≥95 percent at all time points in 68 percent of patients (95 percent CI 62-73 percent), while 26 percent (95 percent CI 21-32 percent) had one or more SO2 levels between 90-94 percent, and 6 percent (95 percent CI 4-10 percent) had SO2 values below 90 percent at one or more time points. The lowest SO2 was 82 percent. The incidence of nausea and vomiting were 16 percent and 7 percent, respectively. Conclusions: Two milligrams IV hydromorphone provides efficacious and rapid pain relief in nonelderly adults presenting to the ED with acute severe pain. However, oxygen desaturation below 95 percent occurred in about one third of patients. Although no noticeable clinical signs of hypoxemia occurred, a conservative interpretation of this finding suggests that 2 mg IV hydromorphone is too much opioid to be given routinely to patients in pain as a single initial dose.